THE EFFECTS OF BORON ADDITION AND PRESULFIDATION TEMPERATURE ON THE HDS ACTIVITY OF A Co-MoS2/Al2O3 CATALYST - Usman Usman; Takeshi Kubota; Yasuaki Okamoto (Universitas Gadjah Mada, 2005)
The effect of boron addition was studied on the hydrodesulfurization (HDS) of thiophene over Co-MoS2/B/Al2O3 (CVD-Co/MoS2/B/Al2O3), which was prepared by a CVD technique using Co(CO)3NO as a precursor of Co. The catalyst was characterized by means of NO adsorption, XPS, Raman Spectroscopy, FTIR, and TEM. The HDS activity of CVD-Co/MoS2/B/Al2O3 catalyst increased as the boron content increased up to about 0.6 and 1.2 wt% B for the catalyst presulfided at 673 and 773 K respectively, followed by a decrease with a further addition of boron loading. In spite of the activity increase, the amount of NO adsorption on MoS2/B/Al2O3 steadily decreased with increasing boron loading, suggesting that the dispersion of MoS2 particles is decreased by the addition of boron. Selective formation of the CoMoS phase on CVD-Co/MoS2/B/Al2O3 was achieved by the CVD technique. The TOF of the HDS over the CVD-Co/MoS2/B/Al2O3 catalyst, defined by the activity per Co atom forming the CoMoS phase, increased as high as 1.6 and 1.9 times for the catalyst presulfided at 673 and 773 K, respectively. It is concluded that the addition of boron weakens the interaction between Mo oxides and Al2O3 surface, promoting the formation of the so called Co-Mo-S